Carcass characteristics and meat quality of purebred Pakchong 5 and crossbred pigs sired by Pakchong 5 or Duroc boar - Rachakris Lertpatarakomol; Rutcharin Limsupavanich; Chanporn Chaosap; Kamon Chaweewan; Ronachai Sitthigripong (My University, 2018)
This study investigated carcass characteristics and meat quality of purebred Pakchong 5, crossbred pigs sired by Pakchong 5, and crossbred pigs sired by Duroc.Forty-eight pigs (average body weight of 22.25 kg) were composed of three groups as purebred Pakchong 5 (PP), Large White×Landrace pigs sired by Pakchong 5 (LWLRP), and Large White×Landrace pigs sired by Duroc (LWLRD). Each group consisted of eight gilts and eight barrows. At 109-day-raising period, pigs were slaughtered, and carcass characteristics were evaluated. Longissimus thoracis (LT) muscles from left side of carcasses were evaluated for meat quality and chemical composition. Data were analyzed using general linear model procedure, where group, sex, and their interaction were included in the model.The PP had greater carcass, total lean, and ham percentages than crossbred pigs (p< 0.05). LWLRP had thicker backfat and more carcass fat percentage than LWLRD (p<0.05). There were no differences (p>0.05) on cutting percentages from tender loin, loin, boston butt, and picnic shoulder among groups. The PP and LWLRP had larger loin eye area (LEA) than LWLRD (p<0.05). Gilts had more loin percentage and lower L* value than barrows (p<0.05). No meat color parameters (L*, a*, and b*) were affected by groups (p>0.05). PP and LWLRP had larger muscle fiber diameters than LWLRD (p<0.05). However, water holding capacity, Warner-Bratzler shear force values, and chemical composition of LT were not affected by group or sex (p>0.05).Pakchong 5 purebred has good carcass and lean percentages. Compared to Duroc crossbred pigs, Pakchong 5 crossbreds have similar carcass and lean percentages, larger LEA, and slightly more carcass fat, with comparable meat quality and chemical composition. Pakchong 5 boars are more affordable for very small- to medium-scale pig producers.
Keywords: Loin; Purebred; Longissimus Thoracis; Large white; BOAR; Carcass weight; Meat and Animal Product Quality